KOMPETENSI PUSTAKAWAN DALAM PEMENUHAN KEBUTUHAN INFORMASI GURU BESAR: STUDI KASUS DI UNIVERSITAS INDONESIA - Kalarensi Naibaho; Mariyah Mariyah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Professor is one of UI's group of users who get special services. This service is called EDS (E-resources Delivery Services) aimed at helping professors meet literacy needs. Librarians download and post specific articles related to the subject of specialization of the professors. During 2016, the response of professors served by EDS is quite encouraging. This study aims to examine how the fulfillment of literature needs of professors in UI and the competence of librarians expected by the professor. The method used is quantitative and qualitative. EDS 2016 performance data is used to analyze EDS productivity. Interview and analysis of professors' responses via e-mail are used to analyze the competence of librarians. The results of the analysis indicate that the professor hopes that UI Library has reference librarian that serves as a competent subject specialist and article submission through continuous EDS as well as relevant to the research topic. Librarians should utilize contacts with assistant professors as they have data and information about the research being conducted. The referral service needs to have a competent team as a reference librarian. Referral librarians should have a wide network with various universities outside UI, especially institutions that have resources that are not owned by UI. The UI library needs to initiate a pattern of cooperation that allows librarians to be involved in the research teams of professors, as literature providers, and to rearrange the delivery schedule of articles by referral librarians, adjusted for the time required for the literature.